2023
DOI: 10.1002/ece3.9858
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomic characterization of two endemic Chinese freshwater crabs of the genus Sinopotamon (Brachyura: Potamidae) and implications for biogeography analysis of Potamidae

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(97 reference statements)
0
0
0
Order By: Relevance
“…In addition, mitochondrial genes have been widely used to analyze genetic diversity [23,24] and population genetic variability in bivalves [25][26][27]. Although the animal mitochondrial gene order remains relatively conserved during long periods of evolution [6,28,29], recent studies have revealed a large number of gene rearrangement events in mitogenomes belonging to different animal Fishes 2023, 8, 528 2 of 17 groups [30][31][32]. The comparison of animal mitochondrial gene arrangements has become a very powerful tool for inferring ancient evolutionary relationships, as rearrangements appear to be unique, generally rare events that are unlikely to arise independently in separate evolutionary lineages [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mitochondrial genes have been widely used to analyze genetic diversity [23,24] and population genetic variability in bivalves [25][26][27]. Although the animal mitochondrial gene order remains relatively conserved during long periods of evolution [6,28,29], recent studies have revealed a large number of gene rearrangement events in mitogenomes belonging to different animal Fishes 2023, 8, 528 2 of 17 groups [30][31][32]. The comparison of animal mitochondrial gene arrangements has become a very powerful tool for inferring ancient evolutionary relationships, as rearrangements appear to be unique, generally rare events that are unlikely to arise independently in separate evolutionary lineages [33,34].…”
Section: Introductionmentioning
confidence: 99%